Romania's Fiscal Structure in View of Euro Adoption. A Multidimensional Analysis - Maria-Isadora Lazar (CES Working Papers, 2014)
The aim of this paper is to conclude whether the adoption of the single currency induced a trend of structural resemblance, and if so, to determine groups of countries with similar fiscal structures inside the Euro Area. Taking into consideration total revenues, indirect taxation, direct taxation and social contributions, we analyzed primary data and completed it with multidimensional classification. Having in view Romania's objective of adopting Euro currency we aim to establish to which subgroup is Romania more similar in terms of fiscal structure and whether this resemblance enhanced since the accession to the European Union.
Keywords: C38; E62; H71; 330; total revenues; indirect taxation; direct taxation; cluster analysis; Euro Area; Romania